2012
DOI: 10.1097/ncc.0b013e31822c47bd
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Support and the Level of Anxiety, Depression, and Quality of Life of Turkish Women With Gynecologic Cancer

Abstract: Social support is a powerful tool that can mediate the effects of difficult life stressors and decrease the incidence of mood disorders, and, therefore, greater importance should be attached to it in the realm of cancer treatment. Supported by the collaborative efforts of family members and healthcare professionals, cancer patients will more easily cope with the drawbacks of their state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 18 publications
10
41
2
2
Order By: Relevance
“…In symptom scales-fatigue, pain, nausea and vomiting, appetite loss, constipation negatively affected the physical wellbeing. This similar finding was found Deshields TL study 14 were the patients physical wellbeing was found to be low & patients reported that fatigue, insomnia, pain were the common complaints. In current study, the most frequent symptoms were fatigue, pain, insomnia, appetite loss and financial problems.…”
Section: Discussionsupporting
confidence: 76%
“…In symptom scales-fatigue, pain, nausea and vomiting, appetite loss, constipation negatively affected the physical wellbeing. This similar finding was found Deshields TL study 14 were the patients physical wellbeing was found to be low & patients reported that fatigue, insomnia, pain were the common complaints. In current study, the most frequent symptoms were fatigue, pain, insomnia, appetite loss and financial problems.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings revealed that the level of social support from family was a significant predictor of depression. This finding was consistent with the research of Pinar et al (2012), Deno et al (2012), andCarpenter et al (2010) who found that social support plays an important role in reducing the frustration experienced during the illness process. In contrast, the study also found that patients perceived less support from healthcare professionals than from family.…”
Section: Discussionsupporting
confidence: 82%
“…A negative association between depression and symptoms has been documented (LloydWilliams et al, 2004;Teunissen et al, 2007). Patients with high social support have been found to be more likely to have lower depression rates (Pinar et al, 2012). Head and neck cancer patients' social support from family members did not have a direct or indirect influence on depression.…”
Section: Introductionmentioning
confidence: 93%
“…While high social support was associated with increased quality of life, it was also associated with reduced anxiety and depression rates (15). Subjects (n = 1930) with low perceived social support reported significantly higher levels of depression, lower scores on all functional scales, and lower global health quality of life scale scores in a nationwide study.…”
Section: Discussionmentioning
confidence: 99%